Manajemen Pembangunan Pada Developer Perumahan (Britania Cilegon) - Fadly Ardiyatna; Rachmi Yanita; Yenny Widianty (Ocean Engineering : Jurnal Ilmu Teknik dan Teknologi Maritim, 2026)
The development of cluster housing requires integrated management involving civil engineering aspects, construction quality control, project management, cost efficiency, time scheduling, and post-construction maintenance. This colloquium study discusses engineering practices in the Britania Cilegon Housing Project developed by PT. MAS Group, focusing on the construction of Phase I consisting of 160 housing units of type 40 and type 51 out of the total planned area of 535 plots. The methods applied in this study included field observations, project document analysis, technical coordination with the developer and contractors, and engineering evaluation of construction implementation and building maintenance processes. The results indicate that land procurement and site preparation were generally carried out effectively; however, the land elevation, which was relatively close to the river level, required stricter supervision of fill work and drainage systems. Housing designs were prepared internally by the developer, while construction activities were divided based on block zones, house types, and Work Order Letters (SPK). Several major issues identified during construction included inconsistencies in work quality among contractors, violations of construction procedures, project delays caused by inefficient allocation of contractor resources, and defects found in roof structures, wall finishes, and wet areas. Control measures were implemented through quality checklists, progress monitoring using bar charts and S-curves, corrective instructions, and penalties in the form of budget deductions when repairs were conducted directly by the developer. This engineering practice demonstrates that successful housing development is strongly influenced by consistent supervision, sustainable design innovation, environmental awareness, and commitment to maintaining residential quality.